Survei Tingkat Keterampilan Pukulan Forehand pada Peserta Ekstrakurikuler Tenis Meja di SMK TI Muhammadiyah Cikampek - Reza Firmansyah; Ruslan Abdul Gani; Siswanto Siswanto (Peneliti.net, 2021)
This research is motivated by the problem, namely the number of exercises that have been carried out by students in the table tennis game, but when the match is still losing or has not achieved the expected achievement. The purpose of this study was to determine the level of forehand drive ability in the table tennis game of extracurricular participants at SMK TI Muhammadiyah Cikampek. This research is quantitative descriptive. The method used is a survey with test and measurement techniques. Subjects in the study were extracurricular participants at SMK TI Muhammadiyah Cikampek totaling 15 students, consisting of 5 male students and 10 female students. The instrument used is a forehand ability test. Analysis of the data used is a quantitative descriptive analysis technique that is in the form of a percentage. The results based on research and discussion show that the skill level of table tennis extracurricular participants at SMK TI Muhammadiyah Cikampek in detail after carrying out a predetermined test, namely skills in the very good category 3 students (20%), in the good category 9 students (60%) and in the medium category 3 students (20%). The key to the level of forehand skills in table tennis extracurricular participants at SMK TI Muhammadiyah Cikampek is categorized as Good